2015
DOI: 10.1007/s13131-015-0639-2
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen content relative to expression of glycogen phosphorylase (GPH) and hexokinase (HK) during the reproductive cycle in the Fujian Oyster, Crassostrea angulata

Abstract: Glycogen, a polymer of glucose, is an important means of storing energy. It is degraded by glycogen phosphorylase (GPH) and hexokinase (HK), glycogen phosphorylase, and hexokinase cDNAs (Ca-GPH and Ca-HK, respectively), which encode the primary enzymes involved in glycogen use, cloned and characterized and used to investigate the regulation of glycogen metabolism at the mRNA level in Crassostrea angulata. Their expression profiles were examined in different tissues and during different reproductive stages. Ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…GSK and PBK expression patterns were nearly the same as those for GP and GDE, which may reflect their regulatory function of glycogen metabolism. Hexokinase and GLUT expression was consistent with that of GS, which provides glycogen synthesis precursors (Martínez‐Quintana & Yepiz‐Plascencia, ; Zeng, Ni, & Ke, ). Pyruvate kinase, PFK and PGK in the glycolysis pathway had similar expression patterns as those for GP and GDE, which may reflect their whereabouts after glycogen decomposition.…”
Section: Discussionmentioning
confidence: 56%
“…GSK and PBK expression patterns were nearly the same as those for GP and GDE, which may reflect their regulatory function of glycogen metabolism. Hexokinase and GLUT expression was consistent with that of GS, which provides glycogen synthesis precursors (Martínez‐Quintana & Yepiz‐Plascencia, ; Zeng, Ni, & Ke, ). Pyruvate kinase, PFK and PGK in the glycolysis pathway had similar expression patterns as those for GP and GDE, which may reflect their whereabouts after glycogen decomposition.…”
Section: Discussionmentioning
confidence: 56%
“…Gametogenesis in triploids is retarded in the reproductive season, since triploid oysters have poorly developed gonads compared to diploids. According to previous studies on diploid Tapes philippinarum (Shpigel and Spencer, 1996 ), Crassostrea gigas (Soudant et al, 1999 ; Dridi et al, 2007 ; Pogoda et al, 2013 ), Ostrea edulis (Houcke et al, 2016 ), and Crassostrea virginica (Zeng et al, 2015 ), large changes in biochemical composition occur in response to gonad development.…”
Section: Introductionmentioning
confidence: 95%
“…Glycogen is the main molecular contributor to flavor quality in bivalves (Berthelin et al, 2000b ; Racotta et al, 2008 ; Zhang et al, 2015 ). Glycogen content decreased is strongly linked with gonad development and gametogenesis in C. gigas (Berthelin et al, 2000b ; Zeng et al, 2015 ). Various studies have confirmed glycogen synthesis and glycogen degradation can be altered by changes of the glycogen synthesis gene ( Ch GS) and glycogen phosphorylase gene ( Ch GP) (Greiwe et al, 1999 ; Bacca et al, 2005 ; Dridi et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the dynamic of the final stages of oocyte maturation, which requires different compounds such as fatty acids, amino acids, electrolytes, purines and pyrimidines, and other metabolites 49 . Regarding metabolites, glucose, glycogen, lipids, and pyruvate were also observed by many authors in different arthropods 51 53 . Furthermore, carbohydrates facilitate oocyte maturation and developmental competence after fertilisation in mammals 49 , 54 , and are important for embryonic development in arthropods 55 , suggesting a highly conserved link between carbohydrate metabolism and oocyte development.…”
Section: Resultsmentioning
confidence: 52%